Estimation of the probability of inversion in assessing thecredibility of expert. A case study - Bukietyńska, Agnieszka; Czekała, Mariusz; Gurak, Marek; Jagodziński, Jacek; Kłosowski, Jarosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is to obtain an objective opinion from the experts. Expertsare evaluated on the basis of the accordance of their preferences with the total preferences.The inversion distribution was applied. This distribution is associated with inversions occurringin the tau-Kendall test. The probabilities obtained as a result of estimation are needed toconstruct the estimator of demand.
Mathematical Economics; 2017; Nr 13 (20); s. 5-14
Keywords: inversions; fashion industry; probability of mistake; estimation